The neuroprotective mechanism of cinnamaldehyde against amyloid-β in neuronal SHSY5Y cell line: The role of N-methyl-D-aspartate, ryanodine, and adenosine receptors and glycogen synthase kinase-3β - Masoumeh Emamghoreishi; Majid Farrokhi; Atena Amiri; Mojtaba Keshavarz (Avicenna Journal of Phytomedicine, 2019)
Objective: Cinnamaldehyde may be responsible for some health benefits of cinnamon such as its neuroprotective effects. We aimed to investigate the cinnamaldehyde neuroprotective effects against amyloid beta (Aβ) in neuronal SHSY5Y cells and evaluate the contribution of N-methyl-D-aspartate (NMDA), ryanodine, and adenosine receptors and glycogen synthase kinase (GSK)-3β, to its neuroprotective effects. Materials and Methods: After seeding the cells in 96-well plates, adenosine (20, 40, 80, and 120 µM), NMDA (20, 40, 80, and 120 µM), and dantrolene (as a ryanodine receptor antagonist; 2, 4, 6, 8, and 16 µM) were added to the medium containing Aβ25-35 and/or cinnamaldehyde. The 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide method was used to assess neurotoxicity and western blot to measure the GSK-3β protein level. Results: Cinnamaldehyde (15, 20, 23, and 25 μM) significantly reversed Aβ-induced toxicity in SHSY5Y neuronal cells. Adenosine (20, 40, 80 and 120 μM) inhibited the neuroprotective effects of cinnamaldehyde (15 μM). NMDA (20, 40, 80, and 120 μM) reduced cinnamaldehyde (15 and 23 μM) neuroprotective effects against Aβ neurotoxicity. Dantrolene (2, 4, 8, and 16 μM) significantly reduced cinnamaldehyde (15 μM) neuroprotective effects. Cinnamaldehyde (15 and 23 μM) suppressed the Aβ-induced increment of GSK-3β protein level.  Conclusion: NMDA and adenosine receptors suppression together with ryanodine receptors stimulation may be relevant to cinnamaldehyde neuroprotective effects against Aβ neurotoxicity. Moreover, the inhibition of GSK-3β may contribute to the cinnamaldehyde neuroprotection.